PEMERIKSAAN PAJAK DAN PERANANNYA PADA KEPATUHAN WAJIB PAJAK DAN PETUGAS PAJAK - Whedy Prasetyo (Jurnal Ekonomi Akuntansi dan Manajemen, 2011)
Self assessment system is considered as effective, if the transparency and law enforcement are becoming essential issues. The law enforcement may be operated through the examination of tax. This examination represents an instrument to determine the compliance, formal or material, main goal of this examination is to investigate and to improve tax compliance. Taxpayers must realize that tax examination is not a form of threat, the understanding of tax regulation and voluntary compliance may reduce this sense of fear. Moreover, tax examination is such desirable assessment to acknowledge whether the tax obligation has been met appropriately and in punctual based on the tax regulations. The objective of this article is to provide knowledge to the taxpayers such that the process or procedure, and also the type, of examination, can be well understood. Taxpayers can able to deal with the tax examination by showing appropriately cooperative attitude and giving the availability or willingness to be examined and to provide the data or particulars required in the tax examination. Indeed, tax examination is an interaction between tax examiner and taxpayers. Some important things should also be discussed during tax examination such as open-case management, re-examination and reconciliation of tax in the audit finance report, and the review of death and tax. Keywords: Tax examination, self assessment, tax compliance, and law enforcement.